DAMPAK PENETAPAN HARGA OLEH TENGKULAK TERHADAP MINAT JUAL HASIL PERTANIAN - Maryani; Sumiati (Faculty of Islamic Economics and Business, 2020)
In general, the determination of the price of coffee by a middleman is to look at it from several aspects, for the first time looking at the prevailing market price method in the market. Both the plus cost methods, based on the amount of costs incurred to produce the product, are added by a certain percentage of the costs. The third method of contribution margin is the difference between the selling price and the variable cost of a product. The four maximum profit methods, where the maximum profit will directly affect the product sales volume.Finally, the method of return on capital, which requires companies to use it as a basis for setting the selling price of products on the production capacity of the company. The results showed that the price-setting variable by the middleman (X) had a positive and significant effect on the interest of coffee agricultural product sales (Y). This condition could be seen from the coefficient of the price-setting variable which was 0.424 and a significance of 0.000 (less than 0.05). Keywords: Pricing, Agricultural Product Sales Interest